An analysis of intellectual capital disclosure in Malaysian IPO prospectuses - Rashid A.A.; Ibrahim M.K.; Othman R. (2023)
The purpose of this study is to analyze the content of prospectuses and determine the factors influencing IC disclosure of 225 sample companies applied for initial listing on the Bursa Malaysia from 2004 to 2008. The extent of IC disclosure is gauged using content analysis methodology. The findings provide evidence on firm's growth, auditor and culture influence on the level of IC disclosure. 2010 IEEE.